Penguatan Pemasaran Digital Dalam Meningkatan Daya Jual Pada UMKM Kue Tradisional Dapur_A2 di Desa Serbajadi Kab. Deli Serdang - J. Prayoga; Rahman, M. Arif Rahman; Welnof Satria (Jurnal Pengabdian Masyarakat, 2023)
Micro, Small, and Medium-sized Enterprises (MSMEs) are the backbone of economies worldwide. In the rapidly evolving digital age, MSMEs hold significant potential for growth and competitiveness through the utilization of digital marketing. This abstract discusses how digital marketing has become a crucial catalyst in elevating MSMEs to higher levels in the business competition. Digital marketing provides MSMEs with easier access to global markets at relatively lower costs compared to traditional marketing. It enables MSMEs to reach a broader and more diverse audience through various online platforms such as social media, search engines, and email marketing. This opens up opportunities for expanding their reach without being limited by geographic constraints. Furthermore, digital marketing allows MSMEs to measure the effectiveness of their campaigns more accurately and comprehensively. Digital data and analytics provide valuable insights into consumer behavior, enabling companies to fine-tune their strategies, identify growth opportunities, and enhance customer retention. However, challenges in implementing digital marketing also exist. At times, MSMEs may face a lack of knowledge and resources to run effective digital marketing campaigns. Additionally, the rapid changes in technology and digital trends can make it difficult for MSMEs to stay updated.